Associations between mental illness, TB risk and migrant status - S.E. Hayward; K.L. Kristensen; A. Deal; J.H. Petersen; T. Lillebaek; S. Hargreaves; M. Norredam; J.S. Friedland (IJTLD Open)
BACKGROUND: TB and mental illnesses are public health priorities that often co-exist, with migrants in high-income countries being at risk for both conditions. This study investigates whether mental illness influences TB risk and examines the impact of migration status. METHODS: A nationwide prospective cohort study was conducted in Denmark from 1994–2015, involving migrants matched 1:6 to Danish-born individuals. Cox regression models, adjusted for age, sex and migrant status, were used to assess the effect of mental disorders on TB risk. RESULTS: Both migrants and non-migrants with mental disorders showed elevated TB incidence (n = 1,189,273). After adjusting for age and sex, the hazard ratio (HR) for TB in those with any mental disorder was 3.62 (95% CI 2.99–4.39, n < 0.001) compared to those without mental disorders. The effect was more substantial in Danish-born individuals (HR 15.51, 95% CI 12.05–19.95, n < 0.001) than in migrants (HR 1.37, 95% CI 0.99–1.90, n = 0.055). Sub-analyses highlighted a significant effect of substance use (HR 5.49, 95% CI 4.46–6.76, n < 0.001) and psychosis (HR 4.19, 95% CI 1.74–10.08, n = 0.001) and borderline significance for affective/anxiety/stress-related disorders (HR 1.64, 95% CI 0.98–2.73, n = 0.058) on TB risk. CONCLUSIONS: People with mental illnesses, particularly psychotic and substance use disorders, have increased TB incidence and represent a high-risk population for targeted screening and treatment. TB programmes should integrate holistic mental health care.